KUALITAS LAPORAN KEUANGAN: APAKAH KETERLAMBATAN LAPORAN AUDIT, KESIBUKAN MITRA AUDIT, KARAKTERISTIK DIREKSI DAPAT MEMPENGARUHI? - Kennardi Tanujaya; Christian (Faculty of Economics and Business University of Mataram, 2023)
Delays in audit reports can be caused by busy audit partners who hold several clients, which can affect the quality of financial reports. This research analyzes the influence of audit partners' busyness and directors' characteristics on the quality of financial reports, with audit report delays as a mediating variable. Using multiple linear regression, this research examines 233 sample data from property and real estate companies listed on the IDX during the 2018-2022 period. The research results show that the size of the board of directors has a significant negative effect on audit report delays. Audit report delays have a significant negative effect, and the directors' expertise has a significant positive effect on the quality of financial reports. Delays in the audit report are not significant in mediating the effect of partner busyness and director characteristics on the quality of financial reports. The results of this research provide new insight into evaluating financial reports, especially regarding delays in audit reports, partners' busyness, and directors' characteristics.